P110 The association between sleep spindles and cognitive function in middle-aged and older men: A community-based study. (7th October 2021) - Parker, J; Melaku, Y; D'Rozario, A; Wittert, G; Martin, S; Catcheside, P; Lechat, B; Teare, A; Appleton, S; Adams, R; Vakulin, A
Abstract: Introduction: The association between sleep spindles and cognitive function and the potential confounding influence of obstructive sleep apnea (OSA) remains uncertain. This study examined cross-sectional associations between sleep spindle metrics and cognitive function outcomes in community-dwelling men. Methods: Men, Androgen, Inflammation, Lifestyle, Environment, and Stress (MAILES) study participants (n=477) underwent home-based polysomnography between 2010–2011 and completed the inspection time task, trail-making test A (TMT-A) and B (TMT-B), and Fuld object memory evaluation. Frontal spindle metrics derived from sleep electroencephalography included occurrence (total no. of sleep spindle events) and slow (11–13 Hz) and fast (13–16 Hz) spindle density (no./min) during N2 and N3 sleep. Results: Men with OSA (any OSA and severe OSA) had significantly impaired sleep spindles (reduced occurrence and densities). In the complete study sample, higher spindle occurrence during N2 sleep was independently associated with faster inspection time (B= -0.44, 95% CI [-0.87, -0.02], p=0.041), whereas higher fast spindle density during N3 sleep was independently associated with worse TMT-B performance (B=20.7, 95% CI [0.55, 40.9], p=0.044). Furthermore, in men with severe OSA (apnea-hypopnea index ≥30/h), higher slow spindle density during N2 sleep was independently associated with worse TMT-A and TMT-B performance, whereas only higher spindle occurrence during N2 sleep was independently associated with worse TMT-A performance (all p<0.05). Discussion: Specific spindle metrics during N2 and N3 sleep are independently associated with cognitive function in an unselected population of men and men with undiagnosed severe OSA. The utility of sleep spindles for predicting cognitive dysfunction and decline requires further investigation.